1994
DOI: 10.1038/ki.1994.314
|View full text |Cite
|
Sign up to set email alerts
|

Localization of connexin43 in rat kidney

Abstract: The localization of connexin43 (Cx 43) in rat kidney was investigated by the indirect immunofluorescence technique with polyclonal antisera raised against Cx 43. Cx 43 is a gap junction protein expressed in a variety of tissues. The typically punctuated gap junction immunofluorescence (GJI) was observed in the renal arterial and arteriolar system. In the renal artery the GJI was concentrated in the media. In the juxtamedullary nephrons, the GJI is particularly abundant in the vascular bundles. There is abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 12 publications
4
62
2
Order By: Relevance
“…Here, we document that, in their WT form, KI32 mice are normotensive and show, within the kidneys, the differential, cellspecific distribution of Cx43 and Cx32 that has been reported in the kidneys of other normal rodents (21,22,40). Thus, Cx32 was prominent among cells of proximal convoluted tubules, whereas Cx43 was mostly found in collecting medullary ducts (22); ECs of inter- and intralobular vessels, including the afferent arterioles (23,41); and glomerular capillaries.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Here, we document that, in their WT form, KI32 mice are normotensive and show, within the kidneys, the differential, cellspecific distribution of Cx43 and Cx32 that has been reported in the kidneys of other normal rodents (21,22,40). Thus, Cx32 was prominent among cells of proximal convoluted tubules, whereas Cx43 was mostly found in collecting medullary ducts (22); ECs of inter- and intralobular vessels, including the afferent arterioles (23,41); and glomerular capillaries.…”
Section: Figurementioning
confidence: 97%
“…This control is mostly achieved by the juxtaglomerular apparatus, which accommodates, in small regions of the kidney, several cell types, including smooth muscle, endothelial, mesangial, macula densa, and renin-producing cells of the afferent arterioles. Cells of each type are connected by gap junctions (16)(17)(18)(19)(20)(21)(22), and other gap junctions further link the ECs, the smooth muscle cells, and the renin-producing cells of the afferent arteriole (19,23,24). Connexin43 (Cx43) and Cx40 appear to be the prominent connexins forming these junctions in vivo (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…It seems most likely that the elevated Ang II may be a compensatory response to an initial blood pressure drop induced by NO. We note, however, that Cx43 might be more directly involved in the control of renin secretion from the juxtaglomerular apparatus (JGA) because Cx43 proteins are extremely abundant in kidney (26,27), where gap junctional communication is extensive, including connections between VSM and endothelium (20). Thus, the deletion of Cx43 in the endothelium might inhibit the communication between endothelium and JGA and result in an altered secretion of renin.…”
Section: Elevated Plasma No Concentration May Be a Primary Effect Ofmentioning
confidence: 99%
“…One of the striking features of MC is that these cells possess extremely high density of GJ (20,21). This unique property indicates a possibility that MC are actively involved in the function of the juxtaglomerular apparatus (22).…”
mentioning
confidence: 96%
“…This unique property indicates a possibility that MC are actively involved in the function of the juxtaglomerular apparatus (22). Like SMC, MC mainly express GJ protein connexin 43 (Cx43) (20). We previously reported that the GJ in MC are critically involved in the transmission of intercellular signal and in the coordination of MC contraction (23).…”
mentioning
confidence: 99%